Characterization of a specific interaction between Escherichia coli thymidylate synthase and Escherichia coli thymidylate synthase mRNA. - Voeller, D M (1995)
Previous studies have shown that human TS mRNA translation is controlled by a negative autoregulatory mechanism. In this study, an RNA electrophoretic gel mobility shift assay confirmed a direct interaction between Escherichia coli (E.coli) TS protein and its own E.coli TS mRNA. Two cis-acting sequences in the E.coli TS mRNA protein-coding region were identified, with one site corresponding to nucleotides 207-460 and the second site corresponding to nucleotides 461-807. Each of these mRNA sequences bind TS with a relative affinity similar to that of the full-length E.coli TS mRNA sequence (IC50 = 1 nM). A third binding site was identified, corresponding to nucleotides 808-1015, although its relative affinity for TS (IC50 = 5.1 nM) was lower than that of the other two cis-acting elements. E.coli TS proteins with mutations in amino acids located within the nucleotide-binding region retained the ability to bind RNA while proteins with mutations at either the nucleotide active site cysteine (C146S) or at amino acids located within the folate-binding region were unable to bind TS mRNA. These studies suggest that the regions on E.coli TS defined by the folate-binding site and/or critical cysteine sulfhydryl groups may represent important RNA binding domains. Further evidence is presented which demonstrates that the direct interaction with TS results in in vitro repression of E.coli TS mRNA translation.